Destination B1 : - Mann, Malcolm (Macmillan, 2008)
Destination Grammar is the ideal grammar and vocabulary practice book for all students preparing to take any B1 level exam. The book contains 28 grammar units and 14 vocabulary units covering a wide range of exercise types, including those found in PET. This is the With Key edition containing an answer key and seven extra photocopiable tests.